Labour, politics, and the state in industrializing Thailand - Brown, Andrew, 1953- (RoutledgeCurzon/City University of Hong Kong South East Asian studies, 2004)
This book focuses on how the state has become entangled in the processes through which workers have been organized, reorganized and disorganized as social and political actors in different historical periods.